A preparation method of long-lasting antibacterial polypropylene melt-blown cloth based on nanocomplexation reaction

By using nanocomplexing reaction technology in polypropylene meltblown cloth, nano zinc oxide and PHMG are mixed and granulated with PP resin to form a long-acting antibacterial polypropylene meltblown cloth, which solves the problem of the lack of antibacterial effect in the existing technology and The problem of insufficient dispersion compatibility achieves efficient and long-lasting antibacterial properties.

CN118621488BActive Publication Date: 2025-02-11TAIYUAN UNIVERSITY OF TECHNOLOGY +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410680797.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-29
Publication Date
2025-02-11
Estimated Expiration
2044-05-29

AI Technical Summary

Technical Problem

The performance of existing polypropylene meltblown cloths is greatly reduced after use for a period of time, the antibacterial effect is not long-lasting, and the dispersion and compatibility of the antibacterial agents are insufficient, resulting in insufficient antibacterial effect.

Method used

Using a nanocomplexing reaction method, nano zinc oxide (ZnO) and polyhexamethylene monoguanide hydrochloride (PHMG) were melt blended and granulated by slices of melt-blown polypropylene (PP) resin to form Compound masterbatches and receive by airflow to form a long-acting antibacterial polypropylene meltblown cloth.

Benefits of technology

Improve the dispersion and compatibility of nano ZnO, enhance the content of antibacterial agents, and achieve full performance of long-acting antibacterial properties. The antibacterial rate can reach 99.9%, and the antibacterial rate remains above 98.5% after long-term soap washing. Rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118621488B_ABST
    Figure CN118621488B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a long-acting antibacterial polypropylene melt-blown cloth based on a nano-complexation reaction, and belongs to the technical field of textile fibers. The invention comprises the following steps: uniformly mixing nano ZnO, PHMG and PP slices, adding the mixture into a twin-screw spinning machine, extruding through a melt-blending high-shear complexation reaction, and then granulating the mixture to obtain a composite masterbatch; the composite masterbatch is melt-blown through a melt-blown machine, and is received through air flow traction to form a long-acting antibacterial polypropylene melt-blown cloth based on a nano-complexation reaction. The invention eliminates the modification process of a conventional nano-particle pre-treatment, shortens the process flow, greatly improves the antibacterial performance and service life of the PP melt-blown cloth, has a good technical effect, and has excellent product performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of textile fibers, and in particular relates to a method for preparing a long-acting antibacterial polypropylene melt-blown cloth based on a nano-complexation reaction. Background Art

[0002] Polypropylene (PP) meltblown cloth is an essential core filter layer for air filtration materials due to its good air permeability and excellent filterability. However, the current mainstream PP meltblown cloth has a single performance and only uses physical principles to intercept and adsorb particulate matter, bacteria, viruses, etc. After a period of use, the performance is greatly reduced. Not only does it not play a protective role, but it also causes waste of resources and secondary environmental pollution. Especially during the high incidence season of influenza, rhinitis, and respiratory infections, almost all application fields have put forward higher requirements for the sustainable killing of bacteria and viruses by meltblown cloth. Therefore, the development of durable antibacterial PP meltblown cloth filter materials has important theoretical and practical value.

[0003] At present, there are two main methods to increase the antibacterial function of PP meltblown cloth, one is material finishing, and the other is doping and blending modification. Finishing is to attach the antibacterial agent to the surface of the material by impregnation, coating and other methods. During use, although the antibacterial effect is good, the process is complicated, the original pore structure inside the material is changed, which greatly affects the filtration efficiency and wind resistance, and the antibacterial agent is easy to fall off, and the antibacterial effect is not lasting; blending modification is to prepare a composite material by melt blending the antibacterial agent with PP, which has the advantages of short process flow and stable structure. However, the molecular weight of meltblown PP raw materials is low, the viscosity is low, and the dispersibility and compatibility of ordinary antibacterial agents after blending are insufficient, resulting in reduced spinnability of meltblown fibers, great difficulty in molding, and the content of antibacterial agents cannot be increased, basically between 0.3% and 1.0%, and the antibacterial effect is not fully exerted, especially the inability to form long-term antibacterial properties.

[0004] Patent application 202211437581.6 discloses a method for improving the antibacterial ability of polypropylene meltblown cloth by using surface-loaded ZnO. The method uses imidazolate ionic liquid, zinc salt, and amino polycationic compound to prepare a mixed solution and spray it on the meltblown cloth. The amount of imidazolate ionic liquid is 0.5-2g / L, and ZnO is 0.5-2g / L. 2+ In the aqueous solution of zinc ions with a content of 1000-4000 mg / L, the amount of amino polycationic compound is 1-4 g / L, and the mass ratio of the solution to the polypropylene melt-blown cloth is 1:20-1:100; finally, by drying at 80-100°C, the rod-shaped nano-ZnO-loaded PP melt-blown cloth with good antibacterial properties can be obtained. However, from the technical process analysis of this method, the water consumption in the post-treatment process is large, and the process flow is long. The fabric structure and filtration performance of the melt-blown cloth will be adversely changed due to the solution treatment.

[0005] Preparation and antibacterial and antistatic properties of silver / reduced graphene oxide loaded polypropylene meltblown nonwovens[J]. Polymer Materials Science and Engineering, 2020, 36(5): 56-63. The method and performance of surface loading of silver / reduced graphene oxide on polypropylene were studied. The results showed that the antibacterial and antistatic properties of the fiber material were improved after surface treatment, but the longitudinal and transverse breaking strength of the PP fiber decreased by 6.08% and 20.53% after surface etching, and the application performance was affected to a certain extent.

[0006] High-performance Electret and Antibacterial Polypropylene MeltblownNonwoven Materials Doped with Boehmite and ZnO Nanoparticles for AirFiltration[J].Fibers and Polymers,2022,23(7):1947-1955.Antibacterial meltblown fabric was prepared by melt blending nanoboehmite and ZnO with polypropylene. The results show that the performance of nano-ZnO doped into boehmite electret nonwoven materials decreases with the increase of boehmite content, mainly because the antibacterial mechanism of zinc oxide antibacterial is to produce active oxygen free radicals through photocatalysis, while the addition of boehmite can reduce its activity, resulting in a decrease in the antibacterial performance of nonwoven materials. This shows that while ensuring the electret filtration efficiency, the ZnO antibacterial agent does not fully exert its antibacterial effect. This document uses nano-ZnO doped into boehmite electret, without adding organic antibacterial agents, and the antibacterial property of the meltblown fabric is insufficient.

[0007] Preparation and Performance of Ultra-Fine Polypropylene Antibacterial Fibers via Melt Electrospinning[J].Polymers, 2020, 12(3): 606. PP / ZnO ultrafine antibacterial fibers were prepared by melt electrospinning. When the ZnO content was greater than 1%, obvious zinc distribution could be seen on the fiber surface, and the mechanical strength decreased with the increase of nano ZnO content, indicating that when the nano ZnO content increased, the compatibility and dispersibility deteriorated, affecting the mechanical properties of the fiber. This document uses melt electrospinning. When the ZnO content was greater than 1%, the compatibility and dispersibility deteriorated, and the product performance deteriorated.

[0008] Preparation and performance study of antibacterial polypropylene fiber for nonwoven fabrics[J]. Synthetic Fiber Industry, 2023, 46(02): 33-37. Antibacterial PP fiber for nonwoven fabrics was prepared by mixing and extruding organic antibacterial agent (KJ-1) with fiber-grade polypropylene (PP) powder. The results showed that when the mass fraction of antibacterial agent KJ-1 was 0.02%, the antibacterial rate of antibacterial PP resin against Escherichia coli and Staphylococcus aureus was greater than 99%. At 230°C, its processing performance was close to that of pure PP resin. The process parameters fluctuated little during the spinning process. The spinneret was used for 22.8 hours, the fiber breaking strength was 1.9 cN / dtex, and the breaking elongation was 325.4%. This shows that the addition of antibacterial agent will affect the rheological properties of PP.

[0009] In summary, the existing methods are prone to problems such as short-lasting antibacterial effect, low content due to insufficient dispersibility and compatibility, and decreased mechanical properties. Therefore, it is of great significance to rationally formulate antibacterial agents and develop a preparation method for long-lasting antibacterial polypropylene meltblown cloth based on nano-complexation reaction to solve the above problems. Summary of the invention

[0010] In order to solve the above technical problems, the present invention proposes a method for preparing a long-lasting antibacterial polypropylene melt-blown cloth based on nano-complexation reaction.

[0011] To achieve the above object, the present invention provides the following technical solutions:

[0012] A method for preparing a long-lasting antibacterial polypropylene meltblown cloth based on a nano-complexation reaction comprises mixing nano zinc oxide (ZnO) and polyhexamethylene guanidine hydrochloride (PHMG), adding meltblown grade polypropylene (PP) resin slices, and obtaining a composite masterbatch after melt blending and granulation. The composite masterbatch is melt-treated and then received by air flow traction to form the long-lasting antibacterial polypropylene meltblown cloth based on the nano-complexation reaction.

[0013] Furthermore, the method for preparing the long-acting antibacterial polypropylene melt-blown fabric based on nano-complexation reaction comprises the following steps:

[0014] (1) drying the nano ZnO and PHMG until the moisture content of both is ≤0.01%;

[0015] (2) mixing the dried nano ZnO, PHMG and melt-blown PP resin chips, and performing melt blending and granulation by a twin-screw extruder to obtain a composite masterbatch;

[0016] (3) drying the composite masterbatch to a moisture content of ≤0.05%;

[0017] (4) placing the dried composite masterbatch in a feeding bin of a melt-blown machine, adopting a single screw to melt extrude, and forming the long-lasting antibacterial polypropylene melt-blown cloth based on the nano-complexation reaction after being pulled and received by air flow.

[0018] Furthermore, in step (1), the drying conditions of the nano ZnO are: heating temperature 90-100° C., vacuum degree -0.1-0.15 MPa, and drying time 5-6 h;

[0019] The drying conditions of the PHMG are: heating temperature 50-60° C., vacuum degree -0.1-0.15 MPa, and drying time 8-9 h.

[0020] Due to the high temperature of each zone of the melt processing, if the added material contains a lot of water, on the one hand, it will sublime into water vapor at high temperature, resulting in too many pores in the matrix, and the stress will be concentrated at the pores, resulting in reduced mechanical properties. On the other hand, high-temperature water vapor will cause the degradation reaction of PHMG, resulting in reduced antibacterial properties.

[0021] Furthermore, in step (2), the mass ratio of the nano ZnO, PHMG and melt-blown grade PP resin chips is (4-6):(1-2):100.

[0022] Furthermore, the nano ZnO is in powder form with an average particle size of 30 nm; the antibacterial agent PHMG is in amorphous powder form; and the melt-blown grade PP resin chips are in granular form with an average diameter of 3 mm.

[0023] Furthermore, in step (2), in order to make the nano ZnO and PHMG fully dispersed and compatible in the melt, produce a complex reaction, and avoid excessive temperature resulting in low viscosity and decomposition reaction, when using a twin-screw extruder for melt blending and granulation, ten zones are configured in the screw thread element, and zones one to four are feeding, conveying and melting zones. After the material is fully melted, two pressure-building zones are set in zones five and six using reverse thread elements. At the same time, triangular meshing elements are configured in zones five and six to increase shear stress. Zone seven is a transmission section, and toothed meshing elements are configured in zone eight to increase the frequency of melt mixing interaction. Zone nine is a homogenizing zone, and zone ten is a head zone. In the present invention, the reverse thread element is used to establish high pressure, and the triangular meshing element is used to increase shear and convection effects, so that PHMG and nano ZnO fully interact and disperse to form a synergistic antibacterial effect.

[0024] The six zones and the die head zone are all equipped with pressure sensors to detect melt pressure.

[0025] Further, the temperature configuration of each zone of the twin-screw extruder is: zone 1 130℃±5℃, zone 2 140℃±5℃, zone 3 150℃±5℃, zone 4 155℃±5℃, zone 5 160℃±5℃; zone 6 165℃±5℃, zone 7 165℃±5℃, zone 8 165℃±5℃, zone 9 170℃±5℃, and die head zone 170℃±5℃;

[0026] The melt pressure in the sixth zone and the die head zone is controlled at 8-9 MPa.

[0027] Furthermore, in step (2), the melt is extruded through the die head and then enters a water cooling tank, where it is cooled and drawn into strands. The strands are dried by a hot air blower and then cut into composite masterbatches by a pelletizer. The cooling water temperature in the water cooling tank is maintained at 20°C ± 5°C.

[0028] Furthermore, in step (3), the drying conditions of the composite masterbatch are: heating temperature 80-90° C., vacuum degree 0.08±0.01 MPa, and drying time 7-8 h.

[0029] Furthermore, in step (4), the single screw melt extrusion is carried out in a single screw extruder, and the temperature of each zone is configured as follows: zone 1 135°C ± 5°C, zone 2 155°C ± 5°C, zone 3 165°C ± 5°C;

[0030] The diameter of the die spinneret hole is 0.35 mm, the hot air temperature is 110°C ± 5°C, and the receiving distance is 40 cm ± 5 cm.

[0031] Furthermore, in order to stabilize, homogenize and remove impurities from the melt, a melt filter and a long-necked tube need to be installed after the screw area. The melt is precisely metered by a metering pump and enters the spinneret. The ejected fibers are stretched and pulled by high-pressure hot air, and collected by a rolling curtain to obtain a long-lasting antibacterial polypropylene melt-blown cloth based on a nano-complexation reaction.

[0032] The principle of the present invention is that nano ZnO particles have inherent problems of poor dispersibility and poor compatibility with organic materials, and cannot be used in a high ratio in the matrix material. Therefore, the present invention proposes to use the organic antibacterial agent PHMG as a bridge, similar to a compatibilizer, to improve the dispersibility of nano ZnO on the one hand, and to improve the compatibility of nano ZnO with the PP matrix on the other hand. However, nano ZnO and PHMG will not react with each other simply and easily. A large number of experiments have shown that conventional technical means cannot make the two have a complex relationship. In addition, the melting range of melt-blown grade PP is 160-165°C. After it is higher than the melting peak temperature, the viscosity is low, the formability is poor, and it is impossible to form spline pellets. Therefore, under such specific background conditions, the present invention develops a twin-screw relatively low temperature combined with multi-zone high-pressure shearing technology. After passing through two high-pressure high-shear zones and one high-convection mixing zone, on the one hand, it avoids the damage and degradation of PP macromolecules caused by excessively high temperatures, resulting in poor molding. On the other hand, it stimulates the frequent interactions between the active hydroxyl groups on the surface of nano-ZnO and the amino groups of PHMG, so that the nano-ZnO and PHMG produce a complex reaction, thereby improving the dispersion and compatibility of the two-phase materials, thereby increasing the content of nanoparticles to about 5wt%, maintaining the lasting expression of antibacterial properties, and achieving better technical effects.

[0033] The present invention also provides a long-acting antibacterial polypropylene melt-blown cloth based on nano-complexation reaction prepared by the above method.

[0034] The present invention also provides application of the long-acting antibacterial polypropylene melt-blown cloth based on nano-complexation reaction in the preparation of antibacterial materials.

[0035] Compared with the prior art, the present invention has the following advantages and technical effects:

[0036] (1) The present invention adds nano ZnO and PHMG to melt-blown grade PP, and uses twin-screw multi-zone high shear granulation and melt-blown spinning technology to make nano ZnO and PHMG produce a certain nano complex reaction, thereby improving the dispersibility and compatibility, and improving the molding conditions of PP, so that the content of the antibacterial agent is increased to about 5wt%, the antibacterial property is fully exerted and maintained, and a long-lasting antibacterial PP melt-blown cloth is obtained.

[0037] (2) The present invention utilizes the temperature of melt extrusion and the high shear environment to produce complexation, eliminating the modification process of traditional nanoparticle pretreatment, shortening the process flow, and greatly improving the antibacterial performance and service life of the PP meltblown cloth, thus having strong market competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0039] Figure 1 The SEM image and EDS element scanning spectrum results of the composite masterbatch of Example 1;

[0040] Figure 2 The SEM image of the fiber obtained for Example 1;

[0041] Figure 3 The results of the colony counts in the culture medium of the blank control sample (left) and the long-acting antibacterial polypropylene melt-blown cloth based on nano-complexation reaction in Example 1 (right);

[0042] Figure 4 The antibacterial rate of the antibacterial melt-blown fabric based on the nano-complexation reaction of the long-lasting antibacterial polypropylene melt-blown fabric after different soap washing times in Example 1;

[0043] Figure 5 This is a schematic diagram of the ten-zone configuration of a twin-screw extruder in Example 1 of the present invention. DETAILED DESCRIPTION

[0044] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0045] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0046] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0047] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0048] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0049] All raw materials used in the embodiments of the present invention are purchased from commercial sources. For example, nano ZnO is purchased from Beijing Boyu Technology Co., Ltd., PHMG is purchased from Hebei Jinhong Chemical Co., Ltd., and melt-blown PP resin chips are purchased from China National Petroleum Corporation.

[0050] The technical solution of the present invention is further illustrated by the following embodiments.

[0051] Example 1

[0052] Preparation of composite masterbatch

[0053] (1) In this embodiment, the nano ZnO is in powder form with an average particle size of 30 nm; the antibacterial agent PHMG is in amorphous powder form; and the melt-blown grade PP resin chips are in granular form with an average diameter of 3 mm.

[0054] Nano ZnO and PHMG were dried in a vacuum oven. The drying process parameters of nano ZnO were: heating temperature 95°C, vacuum degree -0.1MPa, drying time 5h, and the moisture content of nano ZnO powder after drying was 0.01%. The drying process parameters of PHMG powder were: heating temperature 55°C, vacuum degree -0.1MPa, drying time 8h, and the moisture content of PHMG powder after drying was 0.01%.

[0055] (2) using a high-speed mixer to fully mix the dried nano ZnO, PHMG and melt-blown grade PP resin chips, with the mass ratio of the three being 5:1:100;

[0056] (3) Add the mixture obtained in step (2) into a twin-screw extruder, and use the twin-screw extruder to perform melt blending and granulation. The twin-screw screw element is configured with ten zones (see the schematic diagram of the twin-screw ten-zone configuration). Figure 5 ), Zones 1 to 4 are feeding, conveying and melting zones (Zones 1 to 4 correspond to Figure 5 In the fifth and sixth zones, two pressure-building zones are set up by using reverse thread elements, and both are equipped with triangular meshing elements (the fifth and sixth zones correspond to Figure 5 The middle triangle meshing area), seven areas correspond to Figure 5 In the middle transmission section, toothed meshing elements are configured in the eight zones (eight zones correspond to Figure 5 The middle gear meshing area, the ninth area is the homogenizing area, and the tenth area is the die head area. Pressure sensors are respectively configured in the sixth area and the die head area to detect the melt pressure.

[0057] (4) The temperature configuration of each zone of the twin-screw extruder is: zone 1 130°C, zone 2 140°C, zone 3 150°C, zone 4 155°C, zone 5 160°C; zone 6 165°C, zone 7 165°C, zone 8 165°C, zone 9 170°C, and die head zone 170°C;

[0058] (5) The melt pressure in the sixth zone and the die head zone is controlled at 8.5 MPa;

[0059] (6) The melt is extruded through the die head and then enters the water cooling tank to cool the strands. The hot air blower dries the water and the strands are cut into composite masterbatches by a pelletizer. The cooling water temperature in the water cooling tank is maintained at 20°C.

[0060] Preparation of long-lasting antibacterial polypropylene meltblown fabric based on nanocomplexation reaction:

[0061] (1) The composite masterbatch prepared above was dried using a vacuum drum dryer. The drying process parameters were: heating temperature 85° C., vacuum degree 0.08 MPa, drying time 7 h. The moisture content of the composite masterbatch after drying was 0.05%.

[0062] (2) The dried composite masterbatch is placed in the feed bin of the meltblowing machine to prepare the long-lasting antibacterial polypropylene meltblown cloth: the meltblowing machine adopts single screw melt extrusion, and the temperature configuration of each zone of the screw extruder is: 135°C in zone 1, 155°C in zone 2, and 165°C in zone 3. A melt filter and a long neck tube are configured after the screw zone. The melt enters the spinneret after being accurately metered by a metering pump, and the ejected fibers are stretched and pulled by high-pressure hot air. The long-lasting antibacterial polypropylene meltblown cloth based on the nano-complexation reaction is obtained by collecting the fibers through a roller curtain. The diameter of the die spinneret hole is 0.35 mm, the hot air temperature is 110°C, and the receiving distance is 40 cm.

[0063] Example 2

[0064] Preparation of composite masterbatch

[0065] (1) In this embodiment, the nano ZnO is in powder form with an average particle size of 30 nm; the antibacterial agent PHMG is in amorphous powder form; and the melt-blown grade PP resin chips are in granular form with an average diameter of 3 mm.

[0066] Nano ZnO and PHMG were dried in a vacuum oven. The drying process parameters of nano ZnO were: heating temperature 90°C, vacuum degree -0.15MPa, drying time 6h, and the moisture content of nano ZnO powder after drying was 0.01%. The drying process parameters of PHMG powder were: heating temperature 50°C, vacuum degree -0.15MPa, drying time 9h, and the moisture content of PHMG powder after drying was 0.01%.

[0067] (2) using a high-speed mixer to fully mix the dried nano ZnO, PHMG and melt-blown grade PP resin chips, with the mass ratio of the three being 4:1:100;

[0068] (3) Add the mixture obtained in step (2) to a twin-screw extruder, and use the twin-screw extruder for melt blending and granulation. The twin-screw screw element is configured with ten zones, zones one to four are feeding, conveying and melting zones, two pressure-building zones are set up in zones five and six using reverse screw elements, and triangular meshing elements are configured in both, and tooth-shaped meshing elements are configured in zone eight. Zone nine is a homogenizing zone, and zone ten is a die zone. Pressure sensors are respectively configured in zone six and the die zone to detect melt pressure.

[0069] (4) The temperature configuration of each zone of the twin-screw extruder is: zone 1 130°C, zone 2 140°C, zone 3 150°C, zone 4 155°C, zone 5 160°C; zone 6 165°C, zone 7 165°C, zone 8 165°C, zone 9 170°C, and die head zone 170°C;

[0070] (5) The melt pressure in the sixth zone and the die head zone is controlled at 8 MPa;

[0071] (6) The melt is extruded through the die head and then enters the water cooling tank to cool the strands. The hot air blower dries the water and the strands are cut into composite masterbatches by a pelletizer. The cooling water temperature in the water cooling tank is maintained at 20°C.

[0072] Preparation of long-lasting antibacterial polypropylene meltblown fabric based on nanocomplexation reaction:

[0073] (1) The composite masterbatch prepared above was dried using a vacuum drum dryer. The drying process parameters were: heating temperature 80° C., vacuum degree 0.08 MPa, drying time 8 h. The moisture content of the composite masterbatch after drying was 0.05%.

[0074] (2) The dried composite masterbatch is placed in the feed bin of the meltblowing machine to prepare the long-lasting antibacterial polypropylene meltblown cloth: the meltblowing machine adopts single screw melt extrusion, and the temperature configuration of each zone of the screw extruder is: 135°C in zone 1, 155°C in zone 2, and 165°C in zone 3. A melt filter and a long neck tube are configured after the screw zone. The melt enters the spinneret after being accurately metered by a metering pump, and the ejected fibers are stretched and pulled by high-pressure hot air. The long-lasting antibacterial polypropylene meltblown cloth based on the nano-complexation reaction is obtained by collecting the fibers through a roller curtain. The diameter of the die spinneret hole is 0.35 mm, the hot air temperature is 110°C, and the receiving distance is 40 cm.

[0075] Example 3

[0076] Preparation of composite masterbatch

[0077] (1) In this embodiment, the nano ZnO is in powder form with an average particle size of 30 nm; the antibacterial agent PHMG is in amorphous powder form; and the melt-blown grade PP resin chips are in granular form with an average diameter of 3 mm.

[0078] Nano ZnO and PHMG were dried in a vacuum oven. The drying process parameters of nano ZnO were: heating temperature 100°C, vacuum degree -0.1MPa, drying time 5h, and the moisture content of nano ZnO powder after drying was 0.01%. The drying process parameters of PHMG powder were: heating temperature 60°C, vacuum degree -0.1MPa, drying time 8h, and the moisture content of PHMG powder after drying was 0.01%.

[0079] (2) using a high-speed mixer to fully mix the dried nano ZnO, PHMG and melt-blown grade PP resin chips, with the mass ratio of the three being 3:1:50;

[0080] (3) Add the mixture obtained in step (2) to a twin-screw extruder, and use the twin-screw extruder for melt blending and granulation. The twin-screw screw element is configured with ten zones, zones one to four are feeding, conveying and melting zones, two pressure-building zones are set up in zones five and six using reverse screw elements, and triangular meshing elements are configured in both, and tooth-shaped meshing elements are configured in zone eight. Zone nine is a homogenizing zone, and zone ten is a die zone. Pressure sensors are respectively configured in zone six and the die zone to detect melt pressure.

[0081] (4) The temperature configuration of each zone of the twin-screw extruder is: zone 1 130°C, zone 2 140°C, zone 3 150°C, zone 4 155°C, zone 5 160°C; zone 6 165°C, zone 7 165°C, zone 8 165°C, zone 9 170°C, and die head zone 170°C;

[0082] (5) The melt pressure in the sixth zone and the die head zone is controlled at 9 MPa;

[0083] (6) The melt is extruded through the die head and then enters the water cooling tank to cool the strands. The hot air blower dries the water and the strands are cut into composite masterbatches by a pelletizer. The cooling water temperature in the water cooling tank is maintained at 20°C.

[0084] Preparation of long-lasting antibacterial polypropylene meltblown fabric based on nanocomplexation reaction:

[0085] (1) The composite masterbatch prepared above was dried using a vacuum drum dryer. The drying process parameters were: heating temperature 90° C., vacuum degree 0.07 MPa, drying time 7 h. The moisture content of the composite masterbatch after drying was 0.05%.

[0086] (2) The dried composite masterbatch is placed in the feed bin of the meltblowing machine to prepare the long-lasting antibacterial polypropylene meltblown cloth: the meltblowing machine adopts single screw melt extrusion, and the temperature configuration of each zone of the screw extruder is: 135°C in zone 1, 155°C in zone 2, and 165°C in zone 3. A melt filter and a long neck tube are configured after the screw zone. The melt enters the spinneret after being accurately metered by a metering pump, and the ejected fibers are stretched and pulled by high-pressure hot air. The long-lasting antibacterial polypropylene meltblown cloth based on the nano-complexation reaction is obtained by collecting the fibers through a roller curtain. The diameter of the die spinneret hole is 0.35 mm, the hot air temperature is 110°C, and the receiving distance is 40 cm.

[0087] Comparative Example 1

[0088] The same as Example 1, except that PHMG was not added when preparing the antibacterial polypropylene melt-blown cloth.

[0089] Since PHMG was not added when preparing the antibacterial polypropylene melt-blown cloth in this comparative example, the compatibility of nano ZnO with the PP matrix was poor, and the antibacterial polypropylene melt-blown cloth could not be successfully prepared.

[0090] Comparative Example 2

[0091] The same as Example 1, except that step (3) is: adding the mixture obtained in step (2) to a twin-screw extruder, and using the twin-screw extruder for melt blending and granulation. The twin-screw thread element is configured with ten zones, zones one to four are feeding and melting zones, and zones five and six are not configured with reverse thread elements and triangular meshing elements for meshing, but with small-lead thread compression zones, and zone eight is configured with large-lead thread elements for exhaust. Zone nine is a homogenization zone, and zone ten is a die zone. Pressure sensors are respectively configured in zone six and the die zone to detect melt pressure.

[0092] Since high pressure, high shear and high convection mixing were not established in this comparative example, PHMG and nano-ZnO could not fully interact and disperse, could not form a synergistic antibacterial effect, and the expression of antibacterial properties could not achieve the best effect.

[0093] The morphology of the composite masterbatch cross section was observed using a TESCAN MIRA LMS scanning electron microscope, the acceleration voltage was set to 3 kV, and the EDS spectrometer (model Xplore) equipped with the equipment was used to perform point scanning on the nanoparticles exposed on the composite masterbatch cross section. The SEM image and EDS element scanning spectrum results of the composite masterbatch in Example 1 are shown in Figure 1It can be seen that nano ZnO and PHMG are evenly dispersed in the PP matrix without interface separation, indicating good compatibility with the PP matrix. And through the EDS spectrum, it can be seen that the Zn element and O element of nano ZnO and the N element and Cl element spectrum of PHMG appear at the same point, indicating that nano ZnO and PHMG form a whole in the form of complexation, showing synergistic antibacterial effect in the PP matrix.

[0094] The morphology of the meltblown fabric fibers was observed using a JSM-6510LA scanning electron microscope at an electron acceleration voltage of 10 kV. The surface of the meltblown fabric was treated with gold spraying. The SEM image of the fibers obtained in Example 1 is shown in FIG. Figure 2 It can be seen that the diameter distribution of the fibers is relatively uniform, and the average fiber diameter can reach 1.4-1.5μm.

[0095] The antibacterial performance of meltblown fabric was tested in accordance with the national standard GB / T20944.3-2008. The sterilized samples were placed in a 5 The concentration of Escherichia coli and Staphylococcus aureus was shaken for 18 hours, the shaken test solution was aspirated, diluted by 10 times dilution method and then coated on the plate, placed in a constant temperature and humidity incubator for 24 hours, and the colonies were counted after being taken out. The calculation formula of antibacterial rate is as follows:

[0096]

[0097] Where, Y is the antibacterial rate of the sample, W t is the average value of the viable bacterial concentration in the flask (CFU / mL) of the four control samples after 18 hours of shaking contact, Q t It is the average value (CFU / mL) of the viable bacteria concentration in the flask after 18 hours of shaking contact of 4 antibacterial fabric samples.

[0098] The results of the blank control sample (left) and the long-acting antibacterial polypropylene melt-blown cloth based on nano-complexation reaction in Example 1 (right) are shown in the culture medium colony counts. Figure 3 It can be seen from the colony count that the antibacterial property of the antibacterial meltblown cloth can reach 99.9%, indicating that the long-lasting antibacterial polypropylene meltblown cloth based on nano-complexation reaction of the present invention has obvious antibacterial effect.

[0099] Long-term antibacterial performance test of meltblown cloth: Take 10 parts of meltblown cloth of equal weight (taking Example 1 as an example), prepare soap solution according to GB / T3921-2008, and immerse each part in 40°C soap solution for 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, and 5h respectively. After soap washing, rinse the sample with distilled water 5 times and place it in a 40°C oven for drying. The antibacterial rate of each sample is obtained by the above-mentioned antibacterial test method for the dried meltblown cloth, see the attached Figure 4 .

[0100] Depend on Figure 4 It can be seen that the antibacterial rate of the antibacterial meltblown cloth can still be maintained above 98.5% after soaping for 5 hours, showing excellent long-term antibacterial effect.

[0101] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a long-lasting antibacterial polypropylene melt-blown fabric based on nano-complexation reaction, characterized in that: Nano zinc oxide and polyhexamethylene guanidine hydrochloride are mixed, melt-blown grade polypropylene resin slices are added, and composite masterbatch is obtained after melt blending and granulation by a twin-screw extruder. The composite masterbatch is melt-treated and then received by air flow traction to form the long-acting antibacterial polypropylene melt-blown cloth based on nano-complexation reaction; When a twin-screw extruder is used for melt blending and granulation, ten zones are configured in the screw thread element. Zones one to four are feeding, conveying and melting zones. After the material is fully melted, two pressure-building zones are set up in zones five and six using reverse thread elements. At the same time, triangular meshing elements are configured in zones five and six, tooth-shaped meshing elements are configured in zone eight, zone nine is a homogenizing zone, and zone ten is a die head zone. The six zones and the nose zone are all equipped with pressure sensors; The temperature configuration of each zone of the twin-screw extruder is: zone 1 130℃±5℃, zone 2 140℃±5℃, zone 3 150℃±5℃, zone 4 155℃±5℃, zone 5 160℃±5℃; zone 6 165℃±5℃, zone 7 165℃±5℃, zone 8 165℃±5℃, zone 9 170℃±5℃, die head zone 170℃±5℃; The melt pressure in the sixth zone and the die head zone is controlled at 8-9 MPa.

2. The method for preparing a long-acting antibacterial polypropylene melt-blown cloth based on nano-complexation reaction according to claim 1, characterized in that: The following steps are involved: (1) drying nano zinc oxide and polyhexamethylene guanidine hydrochloride until the moisture content of both is ≤0.01%; (2) mixing the dried nano zinc oxide, polyhexamethylene guanidine hydrochloride and melt-blown grade polypropylene resin slices, and performing melt blending and granulation by a twin-screw extruder to obtain a composite masterbatch; (3) drying the composite masterbatch to a moisture content of ≤0.05%; (4) placing the dried composite masterbatch in a feeding bin of a melt-blown machine, adopting a single screw to melt extrude, and forming the long-lasting antibacterial polypropylene melt-blown cloth based on the nano-complexation reaction after being pulled and received by air flow.

3. The method for preparing a long-acting antibacterial polypropylene melt-blown fabric based on nano-complexation reaction according to claim 2, characterized in that: In step (1), the drying conditions of the nano zinc oxide are: heating temperature 90-100° C., vacuum degree -0.1-0.15 MPa, and drying time 5-6 h; The drying conditions of the polyhexamethyleneguanidine hydrochloride are: heating temperature 50-60° C., vacuum degree -0.1-0.15 MPa, and drying time 8-9 hours.

4. The method for preparing a long-acting antibacterial polypropylene melt-blown fabric based on nano-complexation reaction according to claim 2, characterized in that: In step (2), the mass ratio of the nano zinc oxide, polyhexamethylene guanidine hydrochloride and melt-blown grade polypropylene resin slice is (4-6):(1-2):

100.

5. The method for preparing a long-acting antibacterial polypropylene melt-blown fabric based on nano-complexation reaction according to claim 2, characterized in that: In step (3), the drying conditions of the composite masterbatch are: heating temperature 80-90° C., vacuum degree 0.08±0.01 MPa, and drying time 7-8 h.

6. The method for preparing a long-acting antibacterial polypropylene melt-blown fabric based on nano-complexation reaction according to claim 2, characterized in that: In step (4), the single screw melt extrusion is carried out in a single screw extruder, and the temperature of each zone is configured as follows: zone 1 135°C ± 5°C, zone 2 155°C ± 5°C, zone 3 165°C ± 5°C; The diameter of the die spinneret hole is 0.35 mm, the hot air temperature is 110°C ± 5°C, and the receiving distance is 40 cm ± 5 cm.

7. A long-lasting antibacterial polypropylene melt-blown fabric based on nano-complexation reaction, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 6.

8. Use of the long-acting antibacterial polypropylene melt-blown cloth based on nano-complexation reaction as claimed in claim 7 in the preparation of antibacterial materials.

Citation Information

Patent Citations

  • Preparation method of antibacterial polypropylene melt-blown cloth loaded with nano ZnO

    CN115726104A

  • Melt-blown polypropylene with ultra-long antibacterial effect and preparation method and application thereof

    CN111350026A

  • Polypropylene melt-blown non-woven fabric based on composite antibacterial electret master batches and preparation method

    CN113463270A